Enforcing smart legal contracts: Prospects and challenges - Marsha Simone Cadogan (Centre for International Governance Innovation (CIGI), 2023)
Blockchain technology can autonomously perform transactions across various industries and sectors without human involvement, revolutionizing how people do business. These transactions are performed through smart contracts, which consist of coded commands on the blockchain. This paper looks at how to enforce these autonomous agreements using blockchain online terms of use, focusing on common law jurisdictions, specifically Canada. Some of the advantages of buying and selling on the blockchain include reduced business-to-business transaction costs, automated business-to-consumer transactions and the ability to perform traditional services in new ways.
Keywords: 330